Pharmacokinetics behaviors of l-menthol after inhalation and intravenous injection in rats and its inhibition effects on CYP450 enzymes in rat liver microsomes. (3rd October 2019) - Feng, Xiuli; Liu, Yan; Sun, Xiao; Li, Ang; Jiang, Xiaoyan; Zhu, Xiaosong; Zhao, Zhongxi
Abstract: 1. l -Menthol, as a kind of monocyclic terpene, is widely used in inhalation formulations, food and tobacco. The purpose of this study was to investigate the pharmacokinetic behavior of l -menthol as well as its influence on the activities of cytochrome P450 enzymes. 2. The pharmacokinetic behaviors of l -menthol after inhalation (50 mg/kg) and intravenous injection (10 mg/kg) were investigated. A rat liver microsomal model was adopted to elucidate the inhibitory effect of l -menthol on CYP1A2, CYP2C11, CYP2D1/2, CYP2D4, CYP2E1 and CYP3A1 using phenacetin, tolbutamide, omeprazole, dextromethorphan, chlorzoxazone and testosterone as probe drugs, respectively. 3. The plasma concentration reached the C max within 1.0 h (inhalation) and descended with the T 1/2 of 8.53 and 6.69 h for inhalation and i.v. administration, respectively. IC50 for inhibition of l -menthol on CYP 450 enzymes were 4.35 μM for 2D4, 8.67 μM for 1A2, 13.02 μM for 3A1, 14.78 μM for 2D1/2, 234.9 μM for 2C11 and 525.4 μM for 2E1, respectively. 4. The results illustrate the pharmacokinetic process of l -menthol in rats and provide information for further rational applications. l -Menthol had moderate inhibitions on CYP2D4 and 1A2, which might affect the disposition of medicines primarily dependent on these pathways.